Activities of the first wintering party at Asuka Station by the 28th Japanese Antarctic Research Expedition in 1987 - Masaru Ayukawa (National Institute of Polar Research, 1989)
A construction of Asuka Station had been started at the 26th Japanese Antarctic Research Expedition (JARE-26), and all the necessary wintering facilities were finally equipped by mid-February 1987 during JARE-28 operation. The first wintering activities at Asuka Station started immediately thereafter with eight members under the leadership of the present author. Asuka Station is situated at 71°31′S, 24°08′E of 930m a.s.l. The scientific programs consisted of Asuka Station based observations and field and airborne surveys. The observations at Asuka Station were surface observations for meteorological conditions, geomagnetism, earthquake and icequake, gravity earth tide, building strain by snow accumulation, and so forth. The meteorological data were reported to the WMO Data Center twice a day from March 1,1987,under the international index number of 89524. The field surveys were carried out with an airborne magnetometer and iceradar around Sor Rondane Mountains during November and December. The gravity was also measured at every 1km over a span of 160km from the shore Breid Bay to the foot of the Mountains, and the snow accumulation at every 2km. A preliminary survey of terrestrial fauna and flora was also made in the ice free areas of the Mountains. This report gives the details of wintering operations including logistics and a summary of research activities. This publication also includes the information on weather and snowdrift condition around Asuka Station throughout the year.